PENDAMPINGAN PERENCANAAN PEMBANGUNAN SMP DAN MBS (MUHAMMADIYAH BOARDING SCHOOL) PIMPINAN CABANG MUHAMMADIYAH SAWIT BOYOLALI - Guntur Nugroho; Seplika Yadi; Yunita Furi Aristasari; Arini Hidayah (LPPM Universitas Bina Bangsa, 2022)
Muhammadiyah cadre is very necessary to foster youth to bring the organization forward. The future of Muhammadiyah as a whole is closely related to the activities of the Muhammadiyah cadre movement at the Province, District, Sub-district, and Village levels. Sawit Muhammadiyah Sub-District Head (PCM) is a Muhammadiyah organization at the sub-district level located in Boyolali Area. The regeneration activities at PCM are very important things to do, one of which is by providing educational facilities for the Muhammadiyah Junior High School as a regeneration locomotive at sub-district level. Sawit Muhammadiyah Sub-District Head needs assistance and facilities to realize the plan to establish Junior High Schools and manage Muhammadiyah Boarding School (MBS).